Nonhuman Primate Models of Type 1 Diabetes Mellitus for Islet Transplantation - Haitao Zhu; Liang Yu; Yayi He; Bo Wang (Journal of Diabetes Research)
Islet transplantation is an attractive treatment of type 1 diabetes mellitus (T1DM). Animal models of diabetes mellitus (DM) contribute a lot to the experimental studies of islet transplantation and to evaluations of isolated islet grafts for future clinical applications. Diabetic nonhuman primates (NHPs) represent the suitable models of DMs to better evaluate the effectiveness of islet transplantation, to assess new strategies for controlling blood glucose (BG), relieving immune rejection, or prolonging islet survival, and eventually to translate the preclinical data into tangible clinical practice. This review introduces some NHP models of DM, clarifies why and how the models should be used, and elucidates the usefulness and limitations of the models in islet transplantation.